Preventing Sleep Disruption With Bright Light Therapy During Chemotherapy for Breast Cancer: A Phase II Randomized Controlled Trial - Rissling, Michelle; Liu, Lianqi; Youngstedt, Shawn D.; Trofimenko, Vera; Natarajan, Loki; Neikrug, Ariel B.; Jeste, Neelum; Parker, Barbara A.; Ancoli-Israel, Sonia (Frontiers in Neuroscience, 2022)
PURPOSE: The goal of this study was to examine whether daily increased morning light exposure would maintain or improve sleep and the circadian pattern of relatively more activity in the day and less during the night in women undergoing chemotherapy for breast cancer. PATIENTS AND METHODS: Sleep/wake was measured objectively with wrist actigraphy and subjectively with the Pittsburgh Sleep Quality Index (PSQI) prior to and during chemotherapy cycles 1 and 4. Participants were 39 women with newly diagnosed breast cancer, randomized to either 30-minutes of daily morning bright white light (BWL) or dim red light (DRL). The study was registered with the National Institutes of Health ClinicalTrials.gov (Clinical Trials number NCT00478257). RESULTS: Results from actigraphy suggested that compared to the DRL group, women in the BWL group had longer night-time sleep, fewer sleep disturbances during the night, and had fewer and shorter daytime naps at the end of cycle 4 of chemotherapy as well as exhibiting less activity at night and more activity during the day by the end of cycle 4. Results from PSQI indicated that components of sleep quality improved but daytime dysfunction deteriorated during cycle 4 treatment in the BWL group; meanwhile the DRL group used more sleep medications in the treatment weeks which might have led to the improved sleep quality during the recovery weeks of both cycles. CONCLUSION: These results suggest that bright white light therapy administered every morning on awakening may protect women undergoing chemotherapy for breast cancer from nighttime sleep and daytime wake disruption. Randomized clinical trials in larger samples are needed to confirm these findings.